Comparative studies on energy balance components and their inter relations on soybean crop and bare soil in kharif season at Pune situated in semi-arid tract (MAUSAM, 2002)
Comparative studies of radiation balance components at different growth stages on soybean crop and bare soil were made at Central Agrometeorological  Observatory  (CAgMO), Pune.  Continuous measurements of net, reflected and global solar radiations were made over cropped field as well as over bare soil all throughout the growth phases in kharif season of 1995.  Net and reflected radiations and albedo over canopy were higher by 7, 26 and 25 per cent respectively than bare soil.  The net short wave (absorbed) radiation and net long wave (out-going) radiation evaluated over the canopy  were less than those over bare soil by 5 and 20 per cent respectively.               The mean daily net, reflected, net short wave and net long wave (out-going)  radiation were 9.86, 3.86, 15.35 and 5.49 MJm-2 respectively and the albedo was 20 per cent over soybean canopy whereas for bare soil they were 9.23, 3.07, 16.15 and 6.91 MJm-2  and 16 per cent respectively.  The mean daily global  solar radiation during the crop growing  season was 19.20 MJm-2. The highest albedo (26 per cent) of the crop recorded in the 10th  week after sowing  (WAS) was in correspondence to maximum LAI (5.9) observed at pod formation stage.